Pengaruh FOMO, Brand Image, dan Price Consciousness Terhadap Repuchase intention dengan Purchase Decisions Sebagai Variabel Intervening Botol Minum Corkcicle pada Gen Z - Cahyani, Regita; Thobari, Muhammad Burhanuddin; Mujanah, Siti; Fianto, Achmad Yanu Alif (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Technological advancements and increasing market demands are forcing companies to continuously strive to improve the consumer behavior landscape, especially among generation Z. One of the increasingly prominent phenomena is Fear of Missing Out (FOMO), which is the fear of missing out on pleasant or profitable experiences that others are having. This FOMO, triggered by constant exposure to interesting content on social media, encourages generation Z to make implusive purchases. In addition to FOMO, strong brand image and price consciosness also play an important role in purchasing decisions. The data was collected using a questionnaire that had been tested for validity and reliability, and analyzed using IBM SPSS STATISTIK 25 path analysis